1978
DOI: 10.1007/bf01574470
|View full text |Cite
|
Sign up to set email alerts
|

The aarhus county vagotomy trial

Abstract: In a prospective clinical trial, vagotomy for duodenal ulcer (DU) and prepyloric ulcer (PPU) was performed in 748 patients, 353 of whom were randomly allocated to selective gastric vagotomy and drainage (SGV + D), 54 to SGV + antrectomy (A), 273 to parietal cell vagotomy (PCV), and 68 to PCV + D. By 3 months postoperatively, basal acid secretion (BAO) had not stabilized. During the following year patients with SGV + A showed a decrease, while those with the other operations showed a rise in BAO, significant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
2

Year Published

1979
1979
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(18 citation statements)
references
References 6 publications
3
13
2
Order By: Relevance
“…Knight et al [24] observed a 7% incidence of recur rence after PGV in patients with pre-and intrapyloric ulcer, in contrast to the 30% found by Anderson et al [5] and to the results of our study. Contrary to Anderson et al, the previous authors combined the PGV with a drainage operation.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Knight et al [24] observed a 7% incidence of recur rence after PGV in patients with pre-and intrapyloric ulcer, in contrast to the 30% found by Anderson et al [5] and to the results of our study. Contrary to Anderson et al, the previous authors combined the PGV with a drainage operation.…”
Section: Discussioncontrasting
confidence: 56%
“…Because of the imperfection of partial gastrectomy, vagotomy was introduced in the 1940s and today PG V is widely accepted in Europe as the treatment of choice in surgical therapy of chronic duodenal ulcer [1][2][3][5][6][7][8]. This nonrespective procedure leaves the stomach reser voir and the pyloric sphincter intact and has far fewer side effects when compared with other ulcer operations [1][2][3][4][5][6][7][8][10][11][12][13], However, the long-term studies in the late 1970s and early 1980s reported a higher rate of recurrences after PGV than after resection methods [3,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 13 comparable clinical results but there was significantly more diarrhoea after TVP. Kennedy et al (1975) reported that HSV produced significantly less dumping, nausea and bile vomiting than selective vagotomy and gastrojejunostomy without an increased risk of recurrent ulcer (2 per cent in each group).More recently, Amdrup et al (1977) have compared HSV and selective gastric vagotomy without drainage in a randomized trial in which 267 out of 554 patients were followed up after 2 years. The recurrence rates were 8 per cent in each group and there were similar clinical results, although there was significantly less dumping after HSV.…”
mentioning
confidence: 99%
“…More recently, Amdrup et al (1977) have compared HSV and selective gastric vagotomy without drainage in a randomized trial in which 267 out of 554 patients were followed up after 2 years. The recurrence rates were 8 per cent in each group and there were similar clinical results, although there was significantly less dumping after HSV.…”
mentioning
confidence: 99%